Self-Perceived Effect of Halitosis Related to Awareness of Maintaining Dental and Oral Health on Mask Use During the Coronavirus Disease 2019 (COVID-19) Pandemic - Syafara Santos Affadha; Rr. Pipiet Okti Kusumastiwi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The use of masks which have become part of daily activities during the pandemic, of course, causes various impacts, one of which is related to dental and oral health. The use of masks raises awareness of oral health because unhealthy teeth and mouth cause bad breath (halitosis). This study aimed to determine self-perceived halitosis related to awareness of oral health in using masks during the COVID-19 pandemic in the youth generation. Methods: This study was an analytic observational study with a cross-sectional approach. A total of 80 research subjects were included in this study. Participant inclusion criteria were new undergraduate students at the Faculty of Medicine, and Health Sciences, Universitas Muhammadiyah Yogyakarta, Yogyakarta, Indonesia and were willing to participate in the study. This study made observations about self-perceived halitosis related to wearing masks. Observations were carried out by interviews using online social media applications. Data analysis was performed using SPSS software version 25. Results: The majority of research subjects were 18 years old, female, and had good self-perceived halitosis when using masks. The majority of research subjects had good oral health behavior. The results of this study showed that there was no difference between subjects with poor self-perceived and good self-perceived subjects regarding behavior in maintaining oral health, p> 0.05. Conclusion: There is no relationship between self-perceived halitosis related to the use of masks and the behavior of maintaining dental and oral health.